1989
DOI: 10.1073/pnas.86.16.6138
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism by which cellulose triggers cellobiohydrolase I gene expression in Trichoderma reesei.

Abstract: The expression of cellobiohydrolase I mRNA from Trichoderma reesei, measured by Northern blot hybridization, is controlled by the nature ofcarbon sources used in the culture medium. Cellulose and the soluble disaccharide sophorose, but not glycerol or glucose, act as inducers. Cellobiohydrolase I mRNA was undetectable when antibodies to the major members of the cellulolytic system were present in the culture medium prior to the addition of cellulose. These antibodies had no repressive effect if sophorose was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0
7

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(84 citation statements)
references
References 21 publications
7
70
0
7
Order By: Relevance
“…The mechanism by which cellulase formation is triggered by the presence of cellulose in the fungus Trichoderma reesei has recently become a major focus of research: the presence of extracellular cellulose is 'recognized' by conidial-surface-bound constitutive cellulases (Kubicek, 1987;Kubicek et al, 1988;El Gogary et al, 1989), particularly cellobiohydrolase I1 (CBH 11) (Messner et al, 1991), which carry out the initial attack on the cellulose molecule. The small amounts of degradation products arising thereby may then be taken up by the fungus and act as inducers of further cellulase formation .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which cellulase formation is triggered by the presence of cellulose in the fungus Trichoderma reesei has recently become a major focus of research: the presence of extracellular cellulose is 'recognized' by conidial-surface-bound constitutive cellulases (Kubicek, 1987;Kubicek et al, 1988;El Gogary et al, 1989), particularly cellobiohydrolase I1 (CBH 11) (Messner et al, 1991), which carry out the initial attack on the cellulose molecule. The small amounts of degradation products arising thereby may then be taken up by the fungus and act as inducers of further cellulase formation .…”
Section: Introductionmentioning
confidence: 99%
“…The formation of some of these enzymes (e.g. cellobiohydrolase I; endo-fl-l,4-xylanase I) is repressed by glucose [15,16]. It has been reported that the 5'-upstream nt-sequence of the T. reesei gene encoding cellobiohydrolase I (cbhl) shows consensus sequences for binding of a potential CreA-homologue [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that basal expression of CBHII is necessary for the formation of the inducer of the cellulase gene at the growth stage of mycelia on cellulose culture. [40][41][42] These facts indicate that CBHII has a role not only in cellulose hydrolysis but also in the formation of the inducer of cellulases. Recently, Suzuki et al 43) reported a significant transcript level of the CBHII gene from P. chrysosporium, which has a singlecopy gene of the GH6 enzyme on its genome, in a culture containing no carbon source.…”
Section: Evolutionary Tree Of the Catalytic Domains Of Cccel6s Andmentioning
confidence: 81%